Integrating global mental health into international school psychology: Supporting refugee and migrant students amid climate and war-induced displacement. - Diaków, Diana Maria; Christner, Ray W. (International Journal of School & Educational Psychology)
This conceptual paper explores the integration of Global Mental Health (GMH) principles into international school psychology to better serve refugee and migrant students affected by conflict, climate change, and displacement. These students face overlapping challenges – trauma, acculturative stress, and educational disruption – that require culturally responsive, trauma-informed, and systems-oriented interventions. Drawing from interdisciplinary literature and professional standards from GMH, NASP, and ISPA, the paper outlines how school psychologists can adapt assessment, intervention, consultation, and policy advocacy to meet the needs of displaced populations. Emphasis is placed on cross-sector and cross-border collaboration, culturally grounded practices, and capacity building at both local and global levels. By embedding GMH into school psychological services, practitioners can promote equity, resilience, and inclusion for one of the world's most vulnerable student populations.